2014
DOI: 10.1186/1471-2466-14-137
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective observational study of diagnostic accuracy of the Xpert® MTB/RIF assay on fiberoptic bronchoscopy sampling for early diagnosis of smear-negative or sputum-scarce patients with suspected tuberculosis

Abstract: BackgroundFiberoptic bronchoscopy (FOB) is a useful diagnosis tool in low-burden countries for patients with suspected pulmonary tuberculosis (TB) who are smear-negative or sputum-scarce. This study sought to determine the accuracy of the Xpert® MTB/RIF (XP) assay using FOB samples.MethodsWe retrospectively reviewed clinical, radiological, and microbiological characteristics of 175 TB-suspected patients requiring diagnostic FOB (bronchial aspirate or bronchoalveolar lavage) with XP assay. Polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
54
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 27 publications
17
54
2
1
Order By: Relevance
“…Similar yields were documented in studies by Pierrae et al [31] as 25%, Bernard DA et al [32] as 41%, and Khalil KF et al [33] as 39.53%.…”
Section: Diagnostic Yield Of Bronchoscopy Guided Techniques In Llf Tbsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar yields were documented in studies by Pierrae et al [31] as 25%, Bernard DA et al [32] as 41%, and Khalil KF et al [33] as 39.53%.…”
Section: Diagnostic Yield Of Bronchoscopy Guided Techniques In Llf Tbsupporting
confidence: 72%
“…Culture of bronchoscopy sample for MTB was not done because of time factor, cumbersome, and cost effectiveness. Similar yields were documented in studies by Pierrae et al [31] as 80%, Bernard et al [32] as 92.3%, Khalil et al [33] as 91.86%, Lee et al [34] as 81.6%, and Surendra et al [35] as 90%, and few other studies [36][37][38][39] from various authors documented sensitivity between 57% and 75%.…”
Section: Diagnostic Yield Of Bronchoscopy Guided Techniques In Llf Tbsupporting
confidence: 68%
“…In a similar study from France Le Palud et al in 2014 found cough (51.9%) as the main symptom followed by general symptoms (45.1%). 12 In majority of patients in our study more than two symptoms were present. The most common lesions detected by chest imaging were consolidation (33.3%) and fibrocavitary diseases (11.1%).…”
Section: Techniquesmentioning
confidence: 96%
“…Chest imaging was normal in 9.7% cases, whereas in study by Le Palud et al nodules (53.7) were the most common radiological finding followed by Pneumonia (27.1%). 12 Out of 72 clinico-radiologically suspected patients, only 3 were BAL smear positive while another 34 were further detected by CBNAAT giving a total bacteriological figure of 37. Out of 34 CBNAAT positive samples, 3 were resistant to Rifampicin.…”
Section: Techniquesmentioning
confidence: 99%
“…In majority of the studies, microscopy sensitivity ranged from 22% to 41% and specificity from 95% to 100% which is similar to our study findings. (5,6,7) In Agarwal et al (8) study for smear negative samples, the sensitivity and specificity of GeneXpert was 79.1% and 93.1%. Many other studies have the sensitivities and specificities in the range of 57% -75% and 97% -100% respectively.…”
Section: Discussionmentioning
confidence: 99%